Skin Dose Modeling and Measurement in a High Field In-Line MRI-Linac System - Tai, Madiha; Patterson, Elizabeth; Metcalfe, Peter E.; Rosenfeld, Anatoly; Oborn, Bradley M. (Frontiers in Physics, 2022)
The Australian MRI-Linac prototype radiotherapy system has been shown to generate significant entry skin or surface dose increases. This arises from electron contamination focusing towards the isocentre caused by the 1 T MRI field being parallel with the x-ray beam. The aim of this study is to present accurate Monte Carlo modelling of these skin dose changes and to compare with previous experimental measurements. Accurate skin dose modelling will improve confidence in the pathway forward to treatment planning for clinical trials. A COMSOL Multiphysics model of the Australian MRI-Linac system was used to generate a 3D magnetic field map to be used in corresponding Geant4 Monte Carlo simulations. The Geant4 simulations included the x-ray source (6MV Linac), Multileaf Collimators (MLCs) and a 30 cm x 30 cm x 30 cm water phantom located with its front surface at the beam isocentre. Simulations were performed with source to surface distance (SSD) of 1819 mm for nominal field sizes 2 cm x 2 cm, 6 cm x 6 cm and 10 cm x 10 cm. Central axis percentage depth dose (PDD) and surface (or skin) doses at 70um depth were calculated by using high resolution scoring voxels of 10um thickness. The results were compared with corresponding experimental data collected using MOSkinTM on the prototype system. The accurate modelling provides great detail into how the electron contamination is heavily confined and focused towards the central axis within the beam area due to the presence of in-line magnetic field in MRI-Linac. This concentration significantly increases the skin dose up to 320% for the field size 10 cm x 10 cm. For 2 cm x 2 cm and 6 cm x 6 cm, surface skin dose is approximately calculated to be around 128% and 217% respectively as compared to the skin dose in the absence of the magnetic field. The simulation results are in generally good agreement +-10% with previously collected experimental data for the same nominal field sizes. These simulations will provide a solid framework for estimating the skin dose changes in clinically relevant treatment plan scenarios that are envisaged in the near future.